Recycling and reuse of used tyres proceedings of the international symposium organised by the Concrete Technology Unit, University of Dundee and held at the University of Dundee, UK on 19-20 March 2001 - Dhir, Ravindra K.; Limbachiya, Mukesh C.; Paine, Kevin A. (Thomas Telford, 2001)
This book presents the proceedings of an International Symposium organised by the Concrete Technology Unit, University of Dundee which brings together some of the world's leading experts in the field of used tyre recycling.